Peningkatan Kemampuan Pemahaman dan Komunikasi Matematis Siswa SMAN 3 Banda Aceh melalui Penerapan Model Problem Based Learning - Amran Amran; M. Ikhsan; M. Duskri (Didaktik Matematika, 2016)
The purpose of this study to determine enhancement the ability of understanding and communication mathematically by applying the Problem Based Learning (PBL) in the learning activity. The population in this study were students of SMAN 3 Banda Aceh with a sample of two classes. Type of research is experimental with pretest-posttest control group design. The experimental group was treated with a model of learning in the form of PBL and the control group with conventional learning. Data were collected using achievement test and observation sheets during the learning takes place. The results of data analysis showed that 1)there are significant differences in increased ability mathematical understanding of students who received PBL learning compared to conventional learning are reviewed as a whole and based on the level of students, 2) there is an interaction between the factors of student learning at low levels and moderate to increased understanding of mathematical abilities, but no interaction at a high level because the student already has a good ability of mathematical understanding, 3) there are significant differences in enhancement communication skills students acquire mathematical learning by PBL compared to students who received conventional learning is reviewed based on the whole student, but there is no difference if the review is based on the level of the student, 4) there is interaction between the factors of student learning at low levels and moderate to increased mathematical communication but no interaction at a high level because students already have a good mathematical communication skills.